(untitled) (Kairaranga, 2010)
This article describes the informed consent process for an in-progress research masters thesis about the school experiences of senior secondary school students who have funding from Ongoing and Reviewable Resource Scheme (ORRS). It examines this in relation to the ‘hierarchy of gatekeepers’ (Powell & Smith, 2009, Stalker, 1998) and issues of capacity to give informed consent.